An updated phylogeny of the redlip blenny genus Ophioblennius - Naomi S. Lastrucci; Lucas T. Nunes; Alberto Lindner; Sergio R. Floeter (Journal of Fish Biology, 2018)
An updated molecular phylogeny of the blenny genus Ophioblennius , with a focus on two geographically disjunct morphotypes observed in Brazil, is presented. The analyses showed that specimens from the north‐eastern Brazilian coast are the endemic redlip blenny Ophioblennius trinitatis , but specimens from the southern Brazilian coast are conspecific to an undescribed east Atlantic Ocean (Gulf of Guinea) species, previously unknown in Brazil. Possible explanations for this geographical pattern include: natural larval dispersal and rafting across the Atlantic; an unknown ecological attribute that enabled this species to colonize southern Brazil; oil platforms as introduction vectors.